Reading during fully automated driving: A study of the effect of peripheral visual and haptic information on situation awareness and mental workload - Md. Yusof, Nidzamuddin; Karjanto, Juffrizal; Hassan, Muhammad Zahir; Terken, Jacques; Delbressine, Frank L.M.; Rauterberg, Matthias (IEEE, 2022)
This study investigates the effect of peripheral visual and haptic information in providing information about upcoming motions of a fully automated vehicle to an occupant engaging in a non-driving related task, i.e. reading. Two peripheral displays, one visual and the other haptic, were designed and tested. It was hypothesized that the peripheral information would enhance the users’ situation awareness and reduce their mental workload. The study was conducted with 18 participants driven around in a real-road environment in a multi-purpose vehicle that simulated a fully automated vehicle. The peripheral visual and haptic information significantly enhanced situation awareness but did not reduce the mental workload. Implications and future work are discussed.